Stateczność Powłoki Walcowej Wzmocnionej Żebrami - Nowacki, W.; Olesiak, Z. (Engineering Transactions, 1956)
In this paper the buckling problem of a cylindrical shell with longitudinal and transversal ribs is solved in an exact manner. The differential equations of the so-called engineer’s theory of shells due to V. Z. Vlasov are taken as the starting point. The solution, by means of double trigonometric series, leads to a double system of equations (1.7.1) and (1.7.2). Taking the determinant of the system equal to zero we obtain the buckling condition. The cases under review concern only at the edges. For a free support a shell built in at one to four edges, an approximate solution is obtained; a more detailed discussion being given in Ref. [2]. Particular problems are investigated: a shell with transversal ribs. In these problems are discussed shells with uniformly distributed load q or loaded by forces S on the ribs. For the last case (a shell with a longitudinal rib in the middle) the diagrams Ckr = f (q) and Ck = f (M) are presented. In Sec. 4, a solution for a shell reinforced with a dense net of ribs is given, using the model of an orthotropic shell. The net can be composed of longitudinal or transversal ribs or both. A shell with a dense net of ribs and one particular rigid rib is investigated in Sec. 5. The shell with a net of ribs is treated as orthotropic.